Population, agricultural extensification and intensification in the dry and derived savannah zones of Ghana - Codjoe, S.N.A.; Bilsborrow, R.E. (Springer, 2011)
This paper examines the role of population in agricultural practices in food crop production in Ghana. Perspectives from Malthus and Boserup (land use extensification and intensification) and multiphasic response theory are drawn upon to postulate linkages between population and these two forms of response in land use. Data from a 2001 household survey of 504 households in 24 rural localities in two ecologically, climatologically, and culturally different regions of Ghana, viz, the dry and derived savannahs are drawn upon in this study. Descriptive statistics, correlation matrices, and multiple regression are used to explore relationships between population and land use in each region and together. Results show that both agricultural extensification and intensification are common in the derived savannah compared with the dry savannah, and that this is at least partly attributable to the former being characterized by better soils, larger farms, better access to agricultural and non-agricultural economic activities, and more schooling. While there was no evidence of Malthusian impacts on land extensification, this could result from the lack of available unused land. Boserupian intensification was evident in household size linkages with the intensity of labor use. There is also evidence of the theoretically proposed tradeoffs (hypothesized in multiphasic response theory) between extensification and intensification in the derived savannah and the two areas combined, between more land and lower labor intensity and between more tractor use and shorter fallow periods. The paper concludes with important caveats and suggestions for future research, as well as some policy implications for Ghana.
Keywords: Population; food crops; Ghana; Land use; Agricultural intensification; Malthus vs. Boserup; Multiphasic response theory; Household surveys